Infra-auricular Sinus: A Very Rare Case Presentation - Nagalingeswaran, Ahilasamy (Indian J Otolaryngol Head Neck Surg, 2019)
A 22-year-old male patient presented with right infra-auricular sinus since birth with preauricular swelling and discharge on and off since age of 3 years. He had no history of previous surgery. Patient noted frequent swelling and foul smelling discharge inferior to right tragus through a small puncta every 3–6 monthly, resulting in abscess formation and scaring around 1–1.5 cms below and anterior to puncta site. The infra tragal sinus tract and the cyst were completely removed surgically by infra-auricular approach. The histopathology report was suggestive of an infra-auricular preauricular sinus. No recurrence was noted on follow up to 2 years. We report this case for its rarity since less than 5 cases have been reported in literature.